2012
DOI: 10.1097/shk.0b013e318249cb96
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating D-Lactate Levels Predict Risk of Mortality After Hemorrhage and Surgical Trauma in Baboons

Abstract: Patients with hemorrhagic shock and/or trauma are at risk of developing colonic ischemia associated with bacterial translocation that may lead to multiple organ failure and death. Intestinal ischemia is difficult to diagnose noninvasively. The present retrospective study was designed to determine whether circulating plasma D-lactate is associated with mortality in a clinically relevant two-hit model in baboons. Hemorrhagic shock was induced in anesthetized baboons (n = 24) by controlled bleeding (mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Additional studies have confirmed that extended elevations correlate with bacteremia likely due to increased bacterial translocation. Elevated D-lactate levels at 48 hours can be predictive of morbidity and mortality [19,20].…”
Section: Lactatementioning
confidence: 99%
“…Additional studies have confirmed that extended elevations correlate with bacteremia likely due to increased bacterial translocation. Elevated D-lactate levels at 48 hours can be predictive of morbidity and mortality [19,20].…”
Section: Lactatementioning
confidence: 99%
“…The temporal dynamics of tight-junction alterations in the intestinal mucosa, thought to be a basis for barrier dysfunction after IR (32), could partly explain this result. Additionally, experimental studies in primates have shown that serum D-lactate levels can predict mortality in models of hemorrhagic shock (33). This adds to the possible clinical value of D-lactate as a biomarker in settings of intestinal IR.…”
Section: Discussionmentioning
confidence: 99%
“…30 Some of these patients with a history of hypotension will ''respond'' to fluid resuscitation initially only to later die of bleeding. 32 This indicator however is a sign of cellular hypoxia, regardless of the cause. 32 This indicator however is a sign of cellular hypoxia, regardless of the cause.…”
Section: Discussionmentioning
confidence: 99%